PF-04859989 as a template for structure-based drug design: Identification of new pyrazole series of irreversible KAT II inhibitors with improved lipophilic efficiency - Dounay, Amy B.; Anderson, Marie; Bechle, Bruce M.; Evrard, Edelweiss; Gan, Xinmin; Kim, Ji-Young; McAllister, Laura A.; Pandit, Jayvardhan; Rong, SuoBao; Salafia, Michelle A.; Tuttle, Jamison B.; Zawadzke, Laura E.; et al. (Bioorganic & medicinal chemistry letters, 2013)
The structure-based design, synthesis, and biological evaluation of a new pyrazole series of irreversible KAT II inhibitors are described herein. The modification of the inhibitor scaffold of 1 and 2 from a dihydroquinolinone core to a tetrahydropyrazolopyridinone core led to discovery of a new series of potent KAT II inhibitors with excellent physicochemical properties. Compound 20 is the most potent and lipophilically efficient of these new pyrazole analogs, with a kinact/Ki value of 112,000M−1s−1 and lipophilic efficiency (LipE) of 8.53. The X-ray crystal structure of 20 with KAT II demonstrates key features that contribute to this remarkable potency and binding efficiency.